LEXICAL CATEGORIES AS CATEGORIES OF THE REFLECTION-ORIENTED TYPE - Zafar Tillaev Akmalovich (Journal Park Publishing, 2023)
The results of human cognitive activity, reflecting knowledge about the world is recorded in the language in lexical categories that are defined as categories of the reflection-oriented type . Forming a linguistic picture of the world, lexical categories mountains represent the results of the natural categorization of action ness. Knowledge presented in lexical categories becomes the basis for the formation of new conceptual structures that provided by the interpretive function of human thinking. As a result, conceptual structures are formed that reflect the estimated nightly performances based on individual experiences comparing the impact of objects and their characteristics on a person, on the formation of the similarity of objects in the course of metonymic and metaphorical transferences and can have sensual, rational and emotional basis.
Keywords: cognitive activity, the general potential of lexical categories, semantic interpretation.